2016
DOI: 10.1186/s41601-016-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

ANN based directional relaying scheme for protection of Korba-Bhilai transmission line of Chhattisgarh state

Abstract: As it is crucial to protect the transmission line from inevitable faults consequences, intelligent scheme must be employed for immediate fault detection and classification. The application of Artificial Neural Network (ANN) to detect the fault, identify it's section, and classify the fault on transmission lines with improved zone reach setting is presented in this article. The fundamental voltage and current magnitudes obtained through Discrete Fourier Transform (DFT) are specified as the inputs to the ANN. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…It can be observed that % error of the suggested method is lower than error of % earlier methods in [6,9,15,17,25,35,38], which is a feature over earlier methods. The reach setting in [4] and accuracy in [8] is 99.5% and 98.36%, respectively. The reach setting and accuracy of the FES is 99.892% and 99.983% respectively.…”
Section: Comparative Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be observed that % error of the suggested method is lower than error of % earlier methods in [6,9,15,17,25,35,38], which is a feature over earlier methods. The reach setting in [4] and accuracy in [8] is 99.5% and 98.36%, respectively. The reach setting and accuracy of the FES is 99.892% and 99.983% respectively.…”
Section: Comparative Assessmentmentioning
confidence: 99%
“…Furthermore, the two terminal data used in [23,24], whereas the suggested FES used source end data. Furthermore, past papers have published an ANN [4,6,17,25] and the suggested method designed…”
Section: Comparative Assessmentmentioning
confidence: 99%
See 3 more Smart Citations